An Unprecedented Neolignan Skeleton from Chimarrhis turbinata - Cardoso, Carmen L.; Castro-Gamboa, Ian [UNESP]; Bergamini, Giovana M.; Cavalheiro, Alberto José [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Lopes, Márcia Nasser [UNESP]; Araújo, Angela Regina [UNESP]; Furlan, Maysa [UNESP]; Verli, Hugo; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2011)
A lignan with a new skeleton named chimarrhinin (1) was isolated from an extract of the leaves of Chimarrhis turbinata, a Rubiaceae plant species. (13)C NMR spectrometric techniques including 1D and 2D experiments and HRESIMS provided unequivocal structural confirmation of this new C(6).C(3) skeleton type. The relative configuration of 1 was established by 2D (1)H-H analysis and J couplings, while its conformation was evaluated through molecular modeling using the RM1 semiempirical method, with the aid of coupling constants obtained by NMR analysis. The antioxidant activity of the new derivative 1 and two known and previously isolated phenolic derivatives (2 and 3) was investigated. An IC(50) value of 7.50 +/- 0.5 mu mol L(-1) was obtained for the new derivative 1, while 2 and 3 showed IC(50) values of 18.60 +/- 0.4 and 18.50 +/- 0.6 mu mol, respectively.